1968
DOI: 10.1111/j.1399-3054.1968.tb07243.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of (±) ‐Abscisin II Induced Inhibition of Lettuce Seed Germination and Seedling Growth by Kinetin

Abstract: Observations have been made on the effect of synthetic, (±)‐abscisin II (dormin), alone and in combination with gibberellin, kinetin and indoleacetic acid, on seed germination and seedling growth of two strains of lettuce, cv. Attraktion and cv. Hohlblättriger Butter. (±)‐Abscisin II inhibited seed germination and seedling growth in both strains. The inhibitory effect of abscisin II on seed germination as well as seedling growth was completely overcome by kinetin in both dark and light. Gibberellic acid, on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
30
1

Year Published

1968
1968
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 17 publications
5
30
1
Order By: Relevance
“…The role of the phytohormones GA and abscisic acid (ABA) on regulation of germination of the lettuce seeds is important. Application of bioactive GA mimics the effect of R (Kahn and Goss, 1957;Ikuma and Thimann, 1960), whereas application of ABA inhibits germination induced by R or application of bioactive GA (Kahn, 1968;Sankhla and Sankhla, 1968). Endogenous levels of the bioactive GA GA 1 are up-regulated by phytochrome (Toyomasu et al, 1993), and those of ABA are down-regulated by phytochrome or application of GA 1 in lettuce seeds (Toyomasu et al, 1994).…”
mentioning
confidence: 99%
“…The role of the phytohormones GA and abscisic acid (ABA) on regulation of germination of the lettuce seeds is important. Application of bioactive GA mimics the effect of R (Kahn and Goss, 1957;Ikuma and Thimann, 1960), whereas application of ABA inhibits germination induced by R or application of bioactive GA (Kahn, 1968;Sankhla and Sankhla, 1968). Endogenous levels of the bioactive GA GA 1 are up-regulated by phytochrome (Toyomasu et al, 1993), and those of ABA are down-regulated by phytochrome or application of GA 1 in lettuce seeds (Toyomasu et al, 1994).…”
mentioning
confidence: 99%
“…WXe have shown that cytokinins overcome the inhibitoryaction of several natural inhibitors in the germination of the photosensitive Grand Rapids lettuce seed (4,5). There are other reports of cytokinin-inhibitor antagonism in germinationl and dormancy (6,7,10,12,14). Chrispeels and Varner have shown that gibberellic acid (GA3) induced a-amylase synthesis in the excised barley aleurone is inhibited by abscisic acid and revrersed only partially by excess GA) (2).…”
mentioning
confidence: 99%
“…Dark germination of Grand Rapids lettuce seeds is promoted by GA3 (4) and ABA inhibits germination induced by GA3 or light (5,13). Increasing the concentration of GA3 in the presence of ABA does not overcome ABA inhibition unless a cytokinin is also present (5).…”
mentioning
confidence: 99%